4-Phenylbutyric Acid Reduces Endoplasmic Reticulum Stress in Chondrocytes That Is Caused by Loss of the Protein Disulfide Isomerase ERp57. (29th October 2019) - Rellmann, Yvonne; Gronau, Isabel; Hansen, Uwe; Dreier, Rita
Abstract : Objective . The integrity of cartilage depends on the correct synthesis of extracellular matrix (ECM) components. In case of insufficient folding of proteins in the endoplasmic reticulum (ER) of chondrocytes, ECM proteins aggregate, ER stress evolves, and the unfolded protein response (UPR) is initiated. By this mechanism, chondrocytes relieve the stress condition or initiate cell death by apoptosis. Especially persistent ER stress has emerged as a pathogenic mechanism in cartilage diseases, such as chondrodysplasias and osteoarthritis. As pharmacological intervention is not available yet, it is of great interest to understand cartilage ER stress in detail and to develop therapeutics to intervene. Methods . ERp57-deficient chondrocytes were generated by CRISPR/Cas9-induced KO. ER stress and autophagy were studied on mRNA and protein level as well as by transmission electron microscopy (TEM) in chondrocyte micromass or cartilage explant cultures of ERp57 KO mice. Thapsigargin (Tg), an inhibitor of the ER-residing Ca 2+ -ATPase, and 4-Phenylbutyric acid (4-PBA), a small molecular chemical chaperone, were applied to induce or inhibit ER stress. Results . Our data reveal that the loss of the protein disulfide isomerase ERp57 is sufficient to induce ER stress in chondrocytes. 4-PBA efficiently diffuses into cartilage explant cultures and diminishes excessive ER stress in chondrocytes dose dependently, no matter if it is induced by ERp57 KO or stimulation with Tg. Conclusion . ER-stress-related diseases have different sources; therefore, various targets for therapeutic treatment exist. In the future, 4-PBA may be used alone or in combination with other drugs for the treatment of ER-stress-related skeletal disorders in patients.